Perspectivas do aprendizado de máquina no ensino da Engenharia Química - Ishida, Denise Miki Tawaraya (Universidade Federal de São Carlos, 2021)
Machine learning is an area of Artificial Intelligence that can predict results from a large set of data. Therefore, many areas are already benefiting from this new technology, such as credit analysis companies that use this mechanism for fraud detection, entertainment services for a recommendation system and in medicine for disease diagnosis. Currently, machine learning is not very often used in Chemical Engineering, but there are some studies with applications in the area that demonstrate that it can be a tool with great potential for Chemical Engineering. This work is a bibliographical review to understand more about machine learning, what is the learning process, the main tools and studies to exemplify these possible applications of machine learning in Chemical Engineering and emphasize its importance. Because of this potential, it is interesting to approach the subject in the learning of Chemical Engineering so students can have greater contact with machine learning and apply this knowledge in the industry. With this in mind, this work suggests some changes in the curriculum of Chemical Engineering students at Universidade Federal de São Carlos to include machine learning in the Chemical Engineering education
Perspectives of machine learning in Chemical Engineering education
Keywords: Aprendizado de máquina; Ensino de Engenharia Química; Inteligência Artificial; Machine learning; Chemical Engineering Education; Artificial Intelligence; ENGENHARIAS::ENGENHARIA QUIMICA